Dual modification of cellulose with esterification and carbonation in DMSO/DBU/CO2 system as fluorescent additive for pH detection. (October 2022) - Lu, Jiangqin; Lu, Shan; Cao, Qinghua; Huang, Juncheng; Liu, Fei; Na, Haining; Zhu, Jin; Jia, Zhen
Abstract: An easy and effective way to synthesize dual-functionalized cellulose derivatives with processability and fluorescence functionality by one-pot modification of successive esterification and carbonation under mild condition is established with the use of DMSO/DBU/CO2 system. Accordingly, four kinds of dual-functionalized cellulose derivatives with rather good fluorescent response are obtained. After blending the synthesized dual-functionalized cellulose derivative with cellulose acetate as functional additive in solution, cast film with the elastic modulus, stress and strain reaches to 2.2 GPa, 34.1 MPa and 5.7% is prepared. Besides, the cast film also exhibits the ability to detect the pH value at 12–14 with detection accuracy of 0.4 through the change of fluorescent color. This research shows a simple but effective way to prepare dual-functionalized cellulose derivatives for the high-quality applications in field of detection. Graphical abstract: Image 1 Highlights: DMSO/DBU/CO2 system is used to prepare dual-functionalized cellulose derivative. Cellulose derivatives are prepared by one-pot modification under mild condition. Cellulose derivatives have both fluorescence functionality and processability. CA-AFC is a functional additive of cellulose acetate film for pH value detection.